Cover Picture: Monitoring Aqueous Phase Reactions by Operando ATR‐IR Spectroscopy at High Temperature and Pressure: A Biomass Conversion Showcase (Chemistry ‐ Methods 11/2021) - Khalili, Khaled N. M.; Peinder, Peter; Bruijnincx, Pieter C. A.; Weckhuysen, Bert M. (Chemistry methods, 2021)
The Front Cover shows an attenuated Total Reflection Infrared spectroscopy (ATR‐IR) probe monitoring a chemical reaction in the liquid phase, particularly water, at demanding conditions. The light penetrates few microns deep in proximity of the ATR‐IR probe and thus any IR‐active entity in that range is probed. This research systematically addresses the challenges associated with acquiring operando ATR‐IR spectra for liquid/aqueous phase reactions, which is essential for better understanding of chemical reactions in the liquid phase. More information can be found in the Full Paper by Khaled N. M. Khalili et al.